Kremer, Tarnowski, Rydel - związki nie tylko tekstowe - Stachura-Lupa , Renata (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
The paper shows connections between Stanisław Tarnowski and Lucjan Rydel and his family. Tarnowski was a disciple of Józef Kremer, while Rydel was a pupil of Tarnowski. Kremer’s views on art, to some extent, shaped Tarnowski’s aesthetic thought, especially when it comes to the perception of beauty and creative act. Kremer accompanied Tarnowski at the beginning of his scientific career. Rydel used to attend Tarnowski’s speeches in his gymnasium period, and then as a student of the Jagiellonian University. He belonged to a narrow group of Young Poland writers, whose work was appreciated by the critic. He included papers about Rydel in Przegląd Polski. [78] Renata Stachura-Lupa In 1899 Tarnowski welcomed a debut volume by Rydel, appreciating his ‘inherent gift, acquired skill, good taste and musical ear, as well as playing with the difficulty of form,’ which contributed to ‘truly brilliant results.’ He praised the author for ‘his honest feelings’, at the same time noticing the dominance of sadness in his poetry, which was supposed to be typical of ‘young’ poetry, reflecting the depressing mood in the nation, caused by ‘the state of the motherland.’ In 1901 in Przegląd Polski he published a dissertation Nowe kierunki dramatu i „Zaczarowane koło” Lucjana Rydla, in which he made an ‘analysis’ of his disciple’s art. What he found particularly valuable was the method of presenting the countryside, which proved he was well-acquainted with its reality. However, it was only the trilogy Zygmunt August that he regarded as a masterpiece and ‘the best historical tragedy we’ve ever had’.